Resolving the Diagnostic Odyssey of a Patient with an Undefined Neuromuscular Disorder Using Massively Parallel Sequencing Approaches - Yu, Yiliu (Springer, 2020)
IRC-SET 2018 Proceedings of the 4th IRC Conference on Science, Engineering and Technology